Radioactive Iodine for the Treatment of Subclinical Thyrotoxicosis Grade 1 and 2: Outcome of up to 18-Year Follow Up - Phowira, Jason; Coffey, Katherine L.; Bartholomew, Peter H.; Vennart, Nicholas; Moreira, Matheus; Emerson, Hannah; Kennedy, David; Weaver, Jolanta U. (Frontiers in Endocrinology, 2022)
Background Subclinical thyrotoxicosis (SCT) is associated with significant morbidity and mortality, specifically increased risk of atrial fibrillation and cardiovascular death. The management is ill-defined due to the scarcity of randomised controlled studies. Some clinicians recommend radioiodine (RAI) treatment however its long-term outcome is unknown. Therefore, further data is needed to provide robust evidence-based guidelines. Methods A prospective, single-protocol analysis of the outcome of SCT patients (Grade 1; 0.1-0.4 mIU/L and Grade 2; <0.1 mIU/L) treated with mean dose of 427 MBq of I131, followed up for up to 18 years. Thyroid function tests were measured at 4-6 weeks, 3-, 6-, and 12-months post-RAI, and annually thereafter. Cure was defined as achieving a euthyroid/hypothyroid state. Results Seventy-eight patients with a median age of 68 years (range 36-84) and varying aetiology [55 toxic multinodular goitre (TMNG), 10 toxic nodule (TN) and 13 Graves’ disease (GD)] were followed up for a median period of 7.5 years (range 1-18). The cure rate was 100%. The rates of hypothyroidism in TMNG, TN and GD were 23.6%, 30% and 38.5% respectively. The median time to hypothyroidism was 6 and 12 months in GD and TMNG/TN respectively. No differences in outcome between Grade 1 versus Grade 2 were observed. Conclusion RAI using single mean dose of 427 MBq is effective and safe, irrespective of aetiology or grade of TSH suppression. GD patients become hypothyroid within the first year, whilst TMNG/TN for up to 9-years. Thus after 12 months of follow up, annual thyroid function monitoring is advised.